"Em todos os períodos há flores nos sertões": representações sertanejas nas cartas-crônicas de Paulo Bezerra (1985-2016) - Dantas, Brena da Silva (2022)
The objective of this work he was analyze the representations of the sertões in the chronicles of the writer Paulo Bezerra (1933-2017). The main sources of this research were the works Cartas dos Sertões do Seridó (2000), Outras Cartas dos Sertões do Seridó (2004), Novas Cartas dos Sertões do Seridó (2009), Cartas dos Sertões do Seridó – 4th Book (2013) and Últimas Cartas dos Sertões do Seridó (2018). The material used in this study were not ordinary letters of a personal nature, but letters that were sent with the purpose of publishing and disseminating their content, for that reason we will call them as chronicle-letters, based in Silva (2012). These productions were sent by Bezerra to the journalist Woden Madruga, who published them in his column in the newspaper Tribuna do Norte, over the years and with a large volume of chronicle-letters produced, these were gradually published in books. The analysis of the sources was made through the concepts of representation, appropriation and circulation, according to Roger Chartier (2002), which allows us to present the representations created and/or reformulated by Bezerra. The sertões as a category produced to delimit a physical, social and cultural space were thought through authors such as Janaína Amado (1995) in dialogue with other writers who wrote about the Brazilian Sertões, but highlighting the sertão constructed and narrated by Paulo Bezerra.